Knowledge, Attitude and Practice Regarding Breast Cancer and Screening Among Female Health Workers at Birat Medical College Teaching Hospital . - Sapkota, Sulav; Priyadarshini, Mona; Karki, Gyanendra Man Singh; Shakya, Ayushma (Birat Journal of Health Sciences, 2024)
Introduction: In Nepal, breast cancer is the second most common cancer amongst women.Objectives: The objective of this study is to analyze the knowledge, attitudes and practices of health care female professional regarding breast cancer and screening.Methodology: A cross sectional study was done among the female healthcare workers in the department of Medical Oncology from 1st November 2021 to 1st December 2021. Purposive sampling technique was applied for sampling. After consent , questionnaire set regarding the research was provided to the female care professionals. The interview was conducted under the supervision of matron of nursing department. The collected data were analyzed with the help of SPSS Statistic software.Results: One hundred seven female healthcare professionals participated the study during the study time period. The mean age of them was 25.25 years (20-45 years).55% of them had high level of knowledge regarding risk factors of breast cancer .88% of them had high level of knowledge regarding symptoms of breast cancer .75% of them had good knowledge regarding breast cancer treatment modalities. 69% of them were aware that screening helps in prevention of breast cancer amongst which 61% participants agreed for screening themselves for breast cancer . 72% of them were involved in self breast examination .A total of 4.6% of them were unaware of mammograms and 93.4% had never undergone mammogram.Conclusion : Present study demonstrated a good knowledge regarding breast cancer but poor practice regarding breast cancer screening methods among the female health care workers at Birat Medical College Teaching Hospital.